Inhibition of Aldose Reductase by Novel Phytocompounds: A Heuristic Approach to Treating Diabetic Retinopathy. (21st March 2022) - Julius, Angeline; Renuka, Remya Rajan; Hopper, Waheeta; Babu Raghu, P.; Rajendran, Sharmila; Srinivasan, Senthilkumari; Dharmalingam, Kuppamuthu; Alanazi, Amer M.; Arokiyaraj, Selvaraj; Prasath, S.
Abstract : Aldose reductase (ALR2) activation in the polyol pathway has been implicated as the primary mechanism for the progression of diabetic retinopathy. Most of the aldose reductase inhibitors (ARIs), used for the treatment of diabetic complications, were withdrawn due to ineffective treatment and adverse side effects caused by nonspecificity. Epalrestat, a carboxylic acid inhibitor, is the only ARI used for the treatment of diabetic neuropathy, though associated with minor side effects to 8% of the treated population. Our study exploited the interactions of Epalrestat-ALR2 crystal structure for the identification of specific phytocompounds that could inhibit human lens ALR2. 3D structures of plant compounds possessing antidiabetic property were retrieved from PubChem database for inhibition analysis, against human lens ALR2. Among the shortlisted compounds, Agnuside and Eupalitin-3-O-galactoside inhibited lens ALR2 with IC50 values of 22.4 nM and 27.3 nM, respectively, compared to the drug Epalrestat (98 nM), indicating high potency of these compounds as ALR2 inhibitors. IC50 concentration of the identified ARIs was validated in vitro using ARPE-19 cells. The in silico and in vitro approaches employed to identify and validate specific and potent ALR2 inhibitors resulted in the identification of phytocompounds with potency equal to or better than the ALR2 inhibiting drug, Epalrestat.